A Case of Guillain-Barre Syndrome with Significant Lymphocytic Pleocytosis - Izadi, Sadegh; Karimian, Mehdi (International Clinical Neuroscience Journal, 2017)
Guillain-Barre syndrome (GBS) is an immune-mediated polyneuropathy. In the cerebrospinal fluid (CSF) characteristic increased protein without pleocytosis i.e., albuminocytologic dissociation is seen. But cases of GBS with significant CSF lymphocytosis have rarely been reported. Here, we present a 38-year-old man with dysarthria, dysphagia, bilateral facial palsy, and limb weakness with the diagnosis of GBS. Nerve Conduction Study confirmed the diagnosis but interestingly in the CSF study increased protein and lymphocytic predominant pleocytosis were found. Other possible differential diagnoses were ruled out by appropriate paraclinical studies. The patient underwent treatment with intravenous immunoglobulin and showed favorable response.